Prevalence and determinants of goitre among children of South Kordofan state, Sudan, 2021: an urgent need for effective implementation of universal salt iodisation - Azza Elfadil Abdalla; Anfal Mahmoud Altahir; Elfatih A. Hasabo; Salma Salah Alrawa; Amna Mutasim Elazrag; Hayat Abdoallah Ahmed; Hiba Abubakr Ali; Ibrahim Mysara Abdelrazig; Mohamed Yaser Ahmed; Mohamed Alsiddig Alagib; Musab Mohammed Siddig; Rofida Salah Asmally; et al. (Cambridge University Press, 2024)
Abstract Objective: This study aimed to determine the prevalence and determinants of goitre among children aged 6-12 years at South Kordofan state. Design: This was a cross-sectional facility-based study. Setting: The study was conducted in twenty villages of South Kordofan state during a medical mission. Participants: All 575 school-age children (6-12 years) who attended the medical day were examined for clinical assessment of goitre. Results: The prevalence of goitre among children of South Kordofan was 42·8 % (grade 1: 15·7 %, grade 2: 27·1 %). Only 24·2 % of caregivers reported using iodised salt. Mothers working as farmers (OR: 3·209, CI 95 % 1·437, 7·167; P = 0·004) and children of Darforian tribes (OR: 21·799, CI 95 % 2·566, 185·226; P = 0·005) were found to be significantly associated with higher prevalence of goitre among children. This contrasts with children of African tribes, where they were found to have less goitre prevalence (OR: 0·432, CI 95 % 0·213, 0·875; P = 0·02). Iodised salt utilisation (OR = 0·523, CI 95 % 0·320, 0·854; P = 0·01) was found associated with a lower prevalence of goitre. Conclusion: Even though National Iodine Deficiency Disorders control programs were initiated in Sudan more than 25 years ago, the prevalence of goitre among children in South Kordofan state was alarming (42·8 %). Efforts to improve access to iodised salt, increase utilisation and raise awareness are urgently needed.